Output gaps and technological progress in European monetary Union - Maria Antoinette Dimitz (Bank of Finland, 2001)
Output gaps for ten European countries and the USA are estimated based on a CES production function with input augmentation in technological progress.The substitution parameter is estimated from the coefficients of the labour and capital demand functions. Estimation is carried out using Johansen's cointegration method. For six of the eleven countries analysed, the use of the Cobb Douglas form would not be appropriate.The output gap estimates show a similar cyclical pattern for all countries.They remain mostly within b14% except for Finland and Greece.Separating labour-augmenting and capital-augmenting technological progress gives insight into the driving forces of growth for individual countries.
URN:NBN:fi:bof-20140807513
Keywords: 330